LlFH1‐mediated interaction between actin fringe and exocytic vesicles is involved in pollen tube tip growth. Issue 2 (16th January 2017) - Li, Shanwei; Dong, Huaijian; Pei, Weike; Liu, Chaonan; Zhang, Sha; Sun, Tiantian; Xue, Xiuhua; Ren, Haiyun
Summary: Pollen tube tip growth is an extreme form of polarized cell growth, which requires polarized exocytosis based on a dynamic actin cytoskeleton. However, the molecular basis for the connection between actin filaments and exocytic vesicles is unclear. Here, we identified a Lilium longiflorum pollen‐specific formin (LlFH1) and found that it localized at the apical vesicles and plasma membrane (PM). Overexpression of LlFH1 induced excessive actin cables in the tube tip region, and downregulation of LlFH1 eliminated the actin fringe. Fluorescence recovery after photobleaching (FRAP) analysis revealed that LlFH1‐labeled exocytic vesicles exhibited an initial accumulation at the shoulder of the apex and coincided with the leading edge of the actin fringe. Time‐lapse analysis suggested that nascent actin filaments followed the emergence of the apical vesicles, implying that LlFH1 at apical vesicles could initiate actin polymerization. Biochemical assays showed that LlFH1 FH1FH2 could nucleate actin polymerization, but then capped the actin filament at the barbed end and inhibited its elongation. However, in the presence of lily profilins, LlFH1 FH1FH2 could accelerate barbed‐end actin elongation. In addition, LlFH1 FH1FH2 was able to bundle actin filaments. Thus, we propose that LlFH1 and profilin coordinate the interaction between the actin fringe and exocytic vesicle trafficking during pollen tube growth of lily.